Abdominal closed trauma in children. - Vivian Vialat Soto; Eduardo Labrada Arjona; Armando Arriete Vega; Rogelio Rodríguez Castillo; Hermes Hernández (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2005)
Blunt abdominal trauma constitutes 90% approximately of the abdominal injuries in children. Due to the augmented size of the child trunk in relation to their extremities, the abdominal lesions are extremely frequents. The abdominal trauma is present in 20-30% of the patients with serious trauma. It's the second cause of death for accidents after the cranial traumatism in the pediatric patient. We presented the Good Clinical Practices Guideline for Blunt Abdominal Trauma, approved by consensus in the 2nd National Good Clinical Practices Workshop in Pediatric Surgery (Manzanillo, Cuba, September 31 - October 3, 2002).